Pengaruh Likuiditas Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia (Studi Kasus Sebelum Dan Saat Covid 19) - Dwi Suryaningsih; Titik Inayati; Adi Suryanto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
Competition in the business world is getting tougher these days, requiring business people to make and implement the right business strategy, in order to maintain the viability of their business, especially in the difficult conditions when the Covid-19 pandemic hit. Increasing economic development in regions in Indonesia and increasing mobility of business people and the general public are tightening business competition in the transportation services business. The research objective is to determine the effect of liquidity and profitability on firm value with capital structure as an intervening variable in transportation companies listed on the Indonesian Stock Exchange. The type of research in this research is quantitative, with a descriptive and verification approach. The information in this study is secondary data, namely in the form of annual financial reports of companies that go public, which are listed on the Indonesia Stock Exchange from 2018 – 2021. The results of the analysis show that there is an effect of Liquidity, Profitability, on capital structure, Current Ratio has no effect on Debt to Equity Ratio; there is an effect of Profitability on Firm Value, there is an influence of liquidity on firm value through capital structure as an intervening variable; the effect of profitability on firm value through capital structure as an intervening variable; there is an effect of liquidity and profitability on company value through capital structure as an intervening variable in transportation companies on the Indonesia Stock Exchange before and during Covid-19.